Responses to flooding of plant water relations and leaf gas exchange in tropical tolerant trees of a black-water wetland - Herrera, Ana (Frontiers in Plant Science, 2013)
This review summarizes the research on physiological responses to flooding of trees in the seasonal black-water wetland of the Mapire River in Venezuela. Inter-annual variability was found during eight years of sampling, in spite of which a general picture emerged of increased stomatal conductance (gs) and photosynthetic rate (PN) during the flooded period to values as high as or higher than in plants in drained wet soil. Models explaining the initial inhibitory responses and the acclimation to flooding are proposed. In the inhibitory phase of flooding, hypoxia generated by flooding causes a decrease in root water absorption and stomatal closure. An increase with flooding in xylem water potential () suggests that flooding does not cause water deficit. The PN decreases due to changes in relative stomatal and non-stomatal limitations to photosynthesis; an increase in the latter is due to reduced chlorophyll and total soluble protein content. Total non-structural carbohydrates accumulate in leaves but their content begins to decrease during the acclimatized phase at full flooding, coinciding with the resumption of high gs and PN. The reversal of the diminution in gs is associated, in some but not all species, to the growth of adventitious roots. The occurrence of morpho-anatomical and biochemical adaptations which improve oxygen supply would cause the acclimation, including increased water absorption by the roots, increased rubisco and chlorophyll contents and ultimately increased PN. Therefore, trees would perform as if flooding did not signify a stress to their physiology.